Analisis Terjadinya Pneumokoniosis Pada Tenaga Kerja Industri Pengecoran Logam di Koperasi Batur Jaya, Ceper, Klaten - Meita Sari Kusumastuti; Agus Suwarni; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2013)
Dust concentration in the ambient of foundry industry which exceeds the threshold limit value (TLV) is potential to cause respiratory problems for workers, including the accumulation of dust in the lungs which lead to pneumoconiosis. The objective of this study was to determine the relationship between various factors, i.e. dust concentration in workplace, workers’ age and years of service, frequency of mask use, and smoking habit; and the incidence of pneumoconio-sis among workers of Koperasi Batur Jaya foundry industry which is located in Ceper Klaten. The study employed cross sectional survey design, and observed 42 respondents from com-bustion, grinding and finishing chamber units. By using Product Moment Pearson’s correlation test, it was revealed that four out of the five factors under study were significantly related with pneumoconiosis. They were: dust concentration (r=0,454; p=0,03), years of service (r=0,500; p=0,001), mask use (r=-0,538; p<0,001) and smoking habit (r=0,358; p=0,04). One factor i.e. workers’ age was not proved as a significant factor (r=-0,124; p=0,436).